PENGEMBANGAN MEDIA PEMBELAJARAN PENGENALAN BUAH DENGAN TEKNOLOGI AUGMENTED REALITY MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Nadzifah Nadzifah; Suprih Widodo; Nuur Wachid Abdul Majid (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
The current Covid-19 pandemic has caused online learning activities to be carried out at home, including early childhood learning. Learning activities carried out at home tend to be limited because not all parents have interesting and varied learning media. This causes the motivation and enthusiasm of early childhood tends to decrease. Therefore, we need an interesting learning media. In this study, the development of fruit recognition learning media applications using Augmented Reality technology will be carried out. The purpose of this research is to create interactive learning media with Augmented Reality Technology sub-material for the introduction of fruit in Early Childhood Education. This study uses the Multimedia Development Life Cycle (MDLC) method with six stages, namely: concept, design, material collection, assembly, testing, and distribution in the Karangmalang area, In-dramayu city. The expected benefit in this research is the application of learning media can help the learning process of early childhood in recognizing and knowing the benefits for the body. Application testing using blackbox testing with the results of all indicators included in the good category and using SUS testing with an average SUS score of 81. These average results indicate that the system usability level is in the "excellent" or "very good" category.